Chemical Modification on Reactive Dye Adsorption Capacity of Castor Seeds - V. Dharmalingam; A. K. Ramasamy; V. Balasuramanian (E-Journal of Chemistry)
Abstract: The roles played by four major functional groups (amine, carboxyl, azo, hydroxyl groups) in the biomass of castor seeds in adsorption of seven dyes were investigated. These functional groups in castor seeds were chemically modified individually to determine their contribution to the adsorption of ionic dyes. The dyes used were remazol red B, procino yellow, fast green FCF, brilliant cresyl blue, methylene blue, neutral red, red-141. It was found that hydroxyl group inhibited the adsorption of anionic dyes but it was major functional group in the adsorption of cationic dyes, hydroxyl group was important functional group in the adsorption of all seven dyes and the effect of methylation of amino group was not significant on the adsorption of seven dyes.